Can High Performance Be Portable? - Chakravarty, Manuel (Communications of the ACM, 2018)
An introduction is presented in which the author discusses an article in the journal which deals with the Halide image processing language and architecture-specific code optimization, and it mentions portability, algorithms, and how to generate high-performance computer software.